2017
DOI: 10.4103/sni.sni_361_16
|View full text |Cite
|
Sign up to set email alerts
|

Physical and electrical characterization of TexasPEG: An electrically conductive neuronal scaffold

Abstract: Background:Graphene and its derivatives have been shown to be biocompatible and electrically active materials upon which neurons readily grow. The fusogen poly(ethylene glycol) (PEG) has been shown to improve outcomes after cervical and dorsal spinal cord transection. The long and narrow PEGylated graphene nanoribbon stacks (PEG-GNRs) with their 5 μm × 200 nm × 10 nm dimensions can provide a scaffold upon which neurons can grow and fuse. We disclose here the extensive characterization data for the PEG-GNRs.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Furthermore, the determined resistance of 14 MΩ is quite reasonable, when compared to experimentally reported conductivity value (∼10 −7 S/m) for the PEG-600 liquid. 81…”
Section: Equivalent Circuit and Simulation Of Xp Spectramentioning
confidence: 99%
“…Furthermore, the determined resistance of 14 MΩ is quite reasonable, when compared to experimentally reported conductivity value (∼10 −7 S/m) for the PEG-600 liquid. 81…”
Section: Equivalent Circuit and Simulation Of Xp Spectramentioning
confidence: 99%
“…It should be noted that a sharp transection typically generates <10 Newtons (N: SI unit of force) of force versus approximately 26,000 N experienced during clinical SCI, a 2600 times difference. [122] Iseda et al . [58] concluded that “ a single severance, which minimizes damage in the lesion site,…spare(s) nearby cells.…”
Section: The Anatomical Basis Of Spinal Cord Fusionmentioning
confidence: 99%
“…described physical and electrical characterization of Texas PEG, the PEG fusogen combined with graphene nanoribbons (GNR) they developed. [ 25 ] By adding conductive GNR to the fusogen solution, the PEG–GNR mixture is believed to first act as an electrical conduit and then as an electrically active scaffold upon which the neurons will grow, directing their processes across the spinal cord gap. [ 20 ] Kim and his colleagues used PEG alone in their mouse experiment and PEG–GNR in their rat experiment.…”
Section: How To Get Neurons To Grow Across the Severed Cord Endsmentioning
confidence: 99%